Role Entrapment, Emotional Exhaustion, and Severe Perceived Stress in a Nursing Administrator with Maternal Responsibilities: A Mixed-Method Single-Case Study - Jaspher M, Justin; K, Kavichelvi (Young Nurses Journal of Research, 2026)
Background: Even though the number of women in leadership roles in nursing academia is rising, they are still disproportionately responsible for household and caregiving duties. The coexistence of professional, maternal, and household roles may generate cumulative stress exposure. There is still a dearth of empirical data that combines time-use analysis with validated stress measurement in nursing administrators.. The purpose of this study is to investigate the lived experience and perceived stress level of a working mother who works in academic administration at a nursing college.Materials & Methods: Mixed-method single-case study. A 44-year-old nursing administrator completed a 24-hour structured activity schedule and participated in reflective narrative reporting. Perceived stress was assessed using the 10-item Perceived Stress Scale (PSS-10). Qualitative data were analyzed thematically. Quantitative results were compared with published normative values.Results: The participant reported 5.5 hours of sleep per day and participated in about 18 hours of role-related activity. Severe perceived stress was indicated by the PSS-10 score of 34/40. The score matched a Z-value of +3.07 (>99th percentile) when compared to normative female population data (Mean = 13.7; SD = 6.6). Thematic analysis identified persistent role compression, emotional exhaustion, relational strain, identity erosion, and chronic sleep restriction.Conclusion: This case illustrates the extreme stress vulnerability that arises from cumulative professional and domestic demands. It is advisable to reform institutional policies and implement targeted stress management interventions in nursing leaders in order to effectively balance their maternal roles.
Keywords: Perceived Stress; Maternal Responsibilities; Relational Spillover; Sleep deprivation; Working Mother